Advances in Multimodal Imaging Techniques for Immunotherapy of Non-small Cell Lung Cancer - Siyuan CHEN; Linning E; Ronghua WANG (CT Lilun yu yingyong yanjiu)
With the emergence of tumor immunotherapy, the immune status of non-small cell lung cancer (NSCLC) is closely linked to treatment selection. Therefore, it is crucial to identify potential beneficiaries using effective methods prior to treatment. Multimodal imaging techniques are advantageous as they are non-invasive, comprehensive, and repeatable, making them valuable for assessing immune status, evaluating early treatment, and predicting long-term outcomes in NSCLC patients. This article aims to review the progress in the application of CT, MRI and PET/CT in NSCLC immunotherapy.